American Lithuanian printing houses and pressmen (1874–1919) - Raguotis, Bronius (Žurnalistikos tyrimai, 2017)
The paper discusses Lithuanian printing houses, an important field of American Lithuanian press (newspapers and books) history. The main focus of the article are printing house workers and other people related to the activities of printing houses and their work, mode of life, and other issues. Most of the information was found in the periodicals of the discussed period. Data and other important statements were also found in the works of the history of American Lithuanians. Those works were published later on. These sources are not about the history of the printing houses, but their chapters and sections contain factographic data related to the topic. The data were collected from bibliographic works. These works allow identifying various facts from a particular period: the number of printing houses, their place of activity, their owners, publishers, editors, printed material, etc. This paper takes into consideration the works of other scientists and authors and uses them. However, in the author’s opinion, there is no point in repeating what has already been done in covering the history of American Lithuanian printing houses (especially before the year 1904). The paper tries to raise and cover new issues and aspects. The article describes the printing houses of the further period (1904– 1919). Most of the information is about printing house workers, their working conditions, demands, professional unions, etc. Some of the issues of this topic are also reflected in the historiographic part which also includes some more distinct articles. The addendum “List of American Lithuanian Pressmen (1874–1919)“ attached to the article is based on the periodicals, bibliographic publications, encyclopaedias (especially The Boston Encyclopaedia), and other sources. This list should be considered as an attempt which contains gaps, inaccuracies, etc.
Keywords: ...